Experimental wave breaking velocity characterization for monochromatic, bichromatic and irregular waves - Conde, J. M. (2014)
The present work focuses on the comparison between different types of data analysis (time analysis; Fourier transform spectral analysis; wavelet transform spectral analysis; and hodograph representation) applied to Acoustic Doppler Velocimetry (ADV) records of wave orbital velocities. Different wave conditions (monochromatic, bichromatic and irregular) have been tested, for the general purpose of experimentally investigating wave shoaling and breaking over a gentle slope. The analysis of the velocity data, through these methodologies, illustrates other relevant phenomena occurring in the wave propagation, which cannot be depicted by the usual wave gauges. Each of these techniques has advantages and drawbacks, and so they should be complementary.